Epioptics-10 : proceedings of the 43rd course of the International School of Solid State Physics, Erice, Italy, 19-26 July 2008 - Cricenti, Antonio (Science and culture series (Singapore). Physics., 2010)
The book is aimed at assessing the capabilities of state-of-the-art optical techniques in elucidating the fundamental electronic and structural properties of semiconductor and metal surfaces, interfaces, thin layers, and layer structures, and assessing the usefulness of these techniques for optimization of high quality multilayer samples through feedback control during materials growth and processing. Particular emphasis is placed on the theory of non-linear optics and dynamical processes through the use of pump-probe techniques together with the search for new optical sources. Some new applications of scanning probe microscopy to material science and biological samples, dried and in vivo, with the use of different laser sources are also presented. Materials of special interest are silicon, semiconductor-metal interfaces, semiconductor and magnetic multi-layers and III-V compound semiconductors.